EVALUASI KINERJA GURU RUMPUN PAI DI MADRASAH IBTIDAIYAH NEGERI 2 TANJUNG BERINGIN KABUPATEN KAUR - Elvi Marlianti (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2016)
This  study  aims  to  determine the  performance  evaluation PAI clumps  in  the  planning, implementation and evaluation of  learning in  the  State  Islamic  Elementary School  (MIN)  Tanjung Beringin District  Kaur.  These  types  of research, including research evaluation, data  collection method in this research is to use the  techniques of observation, interviews, questionnaires and  documentation. The  conclusion of this paper that  the  teacher performance MIN 2 Tanjung Beringin clumps  of PAI in the  planning of the  learning process  quite  well. Planning is used  in learning is always made  at the  beginning of the  semester.  However, there are weaknesses in the  preparation of the  plan,  namely the  lack of planning time is written  in the plan,  structuring the learning background, development of instructional media  and  learning resources are  not  well planned. 2 MIN teacher performance Tanjung Beringin clump  PAI has been  good  and  in accordance  with the  regulations, both  in  the  open  class, delivering  course  material, using  teaching methods, using  instructional media, classroom  management and  lesson  closes. 2 MIN teacher performance Tanjung Beringin clump  PAI is good  enough to evaluate  conformity with the  provisions.  Planned evaluation conducted by the  teacher MIN 2 Tanjung Beringin already accommodated in  the  lesson  plan,  so already  scheduled. But for  the  evaluation that  is impromptu, its implementation depends on  the  purpose of the  material being  taught